2009
DOI: 10.1160/th08-09-0587
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic fibrinogen infusion reduces bleeding after coronary artery bypass surgery

Abstract: It has been suggested that preoperative fibrinogen plasma concentration is independently associated to postoperative blood loss after cardiac surgery. Theoretically, prophylactic infusion of fibrinogen concentrate may thus reduce postoperative bleeding, but this has not previously been investigated. Twenty elective coronary artery bypass graft (CABG) patients with preoperative plasma fibrinogen levels <3.8 g/l were included in a prospective randomised pilot study. Patients were randomised to receive an infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
241
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(259 citation statements)
references
References 26 publications
13
241
2
3
Order By: Relevance
“…All patients receiving additional coagulation factor concentrates were excluded as well as all patients without measured plasma fibrinogen level prior to fibrinogen infusion and after the number of adverse effects was reported and sufficient increase in plasma fibrinogen was seen after administration of an average 6.5 g; this was larger than the standard dose used in our patient group(2-3 g). One clinical randomized but not blinded trial has been done regarding fibrinogen infusion in cardiac surgery; the study included 20 CABG patients with preoperative fibrinogen <3.8g/L [10]. The primary outcomes were safety related to clinical adverse events and graft occlusion accessed by multi-slice computed tomography (CT).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All patients receiving additional coagulation factor concentrates were excluded as well as all patients without measured plasma fibrinogen level prior to fibrinogen infusion and after the number of adverse effects was reported and sufficient increase in plasma fibrinogen was seen after administration of an average 6.5 g; this was larger than the standard dose used in our patient group(2-3 g). One clinical randomized but not blinded trial has been done regarding fibrinogen infusion in cardiac surgery; the study included 20 CABG patients with preoperative fibrinogen <3.8g/L [10]. The primary outcomes were safety related to clinical adverse events and graft occlusion accessed by multi-slice computed tomography (CT).…”
Section: Discussionmentioning
confidence: 99%
“…It is converted in plasma by thrombin into a fibrin clot at the site of tissue damage in order to minimize blood loss and initiate tissue repair [9]. Administration of prophylactic fibrinogen has been shown to reduce postoperative bleeding after coronary artery bypass graft (CABG) [10] and previous studies have reported an inverse correlation between preoperative concentration of fibrinogen in plasma and the volume of postoperative bleeding after CABG [11][12][13][14][15]. This indicates that preoperative fibrinogen plasma concentration, even within the normal range, is a limiting factor for haemostasis after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…78 Studies also suggest fibrinogen repletion will reduce bleeding and the need for allogeneic blood products. 79 A prospective study of fibrinogen concentrates in 61 patients with bleeding post-CPB noted fibrinogen reduced transfusions compared with placebo (2 U vs 13 U, respectively), and transfusion avoidance was achieved in half of the patients. 1 Other prospective and retrospective cardiac surgical studies, including high-risk ascending aortic replacement surgery, report that fibrinogen repletion with concentrates reduces postoperative bleeding and allogeneic blood product administration.…”
Section: Cardiovascular Surgerymentioning
confidence: 99%
“…There is evidence that the low preoperative fibrinogen concentrations correlate with higher peri-operative blood loss in coronary artery bypass surgery (32,33). Pre-operative prophylactic fibrinogen infusion may be beneficial, although larger trials are required to determine safety and efficacy of this practice (34). Pre-operative hyperfibrinogenaemia is associated with higher all-cause mortality (35), possibly because raised fibrinogen levels are a marker of inflammation, reflecting the presence of a systemic disorder (eg sepsis, acute coronary syndrome).…”
Section: Fibrinogenmentioning
confidence: 99%